Retrospective Study on Incidence of Equine Affections Reported at Veterinary Clinical Complex, Anand, Gujarat, India - Anjana, Ruchikkumar R.; Mahla, Jalendra K.; Parikh, Pinesh V. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Retrospective survey was conducted for last three years of equine cases recorded at Veterinary Clinical Complex, Anand Agricultural University, Anand, Gujarat (India) from January 2016 to December 2018. Total 589 cases with various affections of surgical, gynecological, and medicinal were recorded, which included affections of musculoskeletal system (29.03%), colic (19.52%), wound (16.63%), eye (10.52%), fracture (4.41%), genital system (3.73%), neoplasm (3.39%), sinus, fistula and abscess (2.20%), urinary system (2.03%), digestive system (1.69%), hernia (0.33%) and others (6.45%). Out of different surgical affections musculoskeletal system affections (29.03%) were highest and amongst them 49.65% affection were in ceremonial horses (Dancing), whereas 44.75% affections were recorded during training period. Age wise incidence was found highest in 0 to 5 years age group (64.51%), followed by 6 to 10 years (24.27%) and above 10 years (11.20%) age groups. Seasonal incidence was highest in summer (39.04%), followed by winter (32.59%) and lowest in monsoon (28.35%). Sex wise higher incidences were found in males (58.91%) than in females (41.08%), while breed wise incidences were higher in non-descript breed (52.63%) followed by Kathiawadi (16.63%), Marwadi (15.61%), Kutchhi-Sindhi (14.43%), Thoroughbred (0.33%) and Crossbreds (0.33%). These findings reflected the needs for preventive and curative measures to be adopted in precious equines to reduce losses in equine industry.